Fish consumption benefits and PFAS risks: Epidemiology and public health recommendations - Ali Hamade (Toxicology Reports)
Finfish and shellfish intake (collectively referred to as fish) has been associated with health benefits, although fish often have chemical contaminants that are separately associated with health risks. The presence of chemical contaminants, however, does not inherently pose a health risk and optimizing the benefits is desirable for individual and population health. Reference doses (RfDs) and other comparison values that estimate contaminant or pollutant safety thresholds typically do not account for the benefits of the foods that carry them (e.g., fish, eggs, fruit, vegetables). Rather, these numbers are typically applied uniformly for various media such as food, soil, and water. This paper summarizes principal epidemiology studies on per- and polyfluoroalkyl substances (PFAS)-associated noncancer health indicators used by the United States Environmental Protection Agency (EPA) to develop RfDs for PFAS and compares these with the same health outcomes associated with seafood intake. Moreover, it frames these findings in relation to varying human PFAS exposures, fish intake amount, and fish type when the information is available. Further, it presents brief overviews of both general population temporal PFAS exposure trends and PFAS fish contaminant data in the United States. Finally, it discusses approaches that risk assessors and policy makers can consider in developing their fish consumption recommendations in relation to PFAS. In brief, epidemiology studies show that the benefits of fish intake generally counter the risks of PFAS exposure based on four noncancer health endpoints that EPA identified as having the greatest strength of evidence for PFAS health effects.